CHOOSING A TRACTION SYSTEM FOR MALAYSIAN PUBLIC TRANSPORT: LIFECYCLE COST AND SUSTAINABILITY - ZARINA ABDUL MUNIR; IRWAN IBRAHIM; MOHD HAFIZ ZULFAKAR; SARINAH SABAR; MARHANI MOHAMED ANUAR (Quantum Journal of Social Sciences and Humanities, 2026)
This research study evaluates the lifecycle cost and sustainability performance of public transport traction systems in Malaysia, focusing on diesel, electric, battery electric, hybrid, and hydrogen technologies. A quantitative approach integrating total cost of ownership and lifecycle assessment is applied using secondary data and simulation modelling. The research findings show that diesel systems remain cost attractive only in the short term but perform poorly in long term economic and environmental terms. Battery electric systems demonstrate the most balanced performance, offering lower operating costs and significant emissions reduction despite higher capital investment. Hydrogen systems exhibit strong environmental potential but remain economically unviable under current technological and infrastructure conditions. The research study also highlights critical Malaysian challenges, particularly charging infrastructure, grid capacity, and policy coordination. Overall, the results suggest that a phased transition toward electrification, supported by integrated infrastructure and policy alignment, is the most viable pathway for sustainable public transport development.